Managing a non formal educational experience: the Literature and creativity project - Ceciliano Piedra, Ana Cristina (2025)
Literature and creativity was a nonformal educational project developed at “la Casa Jiménez Sancho” in Cartago, Costa Rica, between April 5 and December 5, 2024. It was created as a proposal for collective, intergenerational, and women-led construction that, through weekly sessions and with two central elements such as literature and creativity, promotes innovative management for reading spaces commonly known as reading clubs. This article aims to analyze the experience management process by developing a systematization that demonstrates the relationship between management and the projects' results obtained, from the author, project manager and mediator's perspective. To this end, an analytical process is constructed based on Morin's complexity theory, complemented by an alternative systematization approach proposed by Jara and Díaz, guided by the established central theme: Exploration of the nonformal management elements and their impact on the management results obtained in a nonformal educational project. As a result of this experience, it is evident that a different approach to educational management must begin by managing projects and spaces from diverse theoretical and methodological perspectives, allowing consideration of management stages inherent to projects. Furthermore, it is concluded that managing these stages is a dynamic process that enables a shift in perspective when promoting other types of nonformal educational spaces.